the Generative Engine Optimization (GEO) Strategy In Maintaining Corporate Reputation Authenticity In The Artificial Intelligence Era: A Conceptual Study On Goto Group - Septian Adhi Nugroho Septian; Bagas Ari Prasetyo; Alif Putra Pratama; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
This conceptual research is driven by the fundamental shift in the global communication landscape from keyword-based Search Engine Optimization (SEO) toward generative AI-driven answer mechanisms. As public information consumption transitions to narrative synthesis produced by Large Language Models (LLMs), corporate entities face significant risks regarding informational authority and